Regulatory mechanisms of post-translational modifications on autophagic flux in neurons following ischemic stroke - Liling Yu; Wenting Zhuang; Xiong Liu; Hongqiong He; Yihao Deng; Hongyun He (Molecular Biology Reports, 2026)

A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

Characterization and modification of chickpea husk dietary fibers: Potential applications in gummy candy and emulsion-based food products - Xiangyu Liu; Yifan Zhang; Liang Wang; Minwei Zhang; Fen Li; Huiling Yan; Kaiwen Wu; Feng Zhang; Qiao Zhang; Jun Liu; Chunlan Zhang; Liling Wang; et al. (Food Hydrocolloids, 2026)

Engineered aptamer-confined hydrogel for label-free detection of heavy-metal ions with enhanced interference tolerance - Long Bai; Xiuxiu Wu; Lei Huang; Haohao Chen; Jinsong Yu; Ziqing Ye; Min Yuan; Hui Cao; Liling Hao; Fengqin Yin; Tai Ye; Fei Xu (Food Chemistry, 2026)

Polyurethane grouting materials for infrastructure reinforcement in cold regions: State of the art and perspectives - Tan Liling; Guo Ming; Yu Wenbing; Han Fenglei; Li Guo; Gao Meng (Cold Regions Science and Technology, 2026)

Mediation role of gut microbiota in the association between ambient fine particulate matter components and cardiovascular disease: Evidence from a China cohort - Shaokun Yang; Rui Yu; Fen Yang; Jiawei Li; Lele Wang; Gonghua Wu; Liling Chen; Tingting Yang; Zhuoma Duoji; Yanjiao Wang; Xufang Gao; Yuanyuan Liu (Environmental Research, 2025)

Fluorescent nanozyme for the dual-mode detection of tetracycline: Aggregation-induced luminescence and boosting peroxidase-like activity - Tai Ye; Long Bai; Jinsong Yu; Weiyan Shi; Min Yuan; Juncheng Wang; Hui Cao; Liling Hao; Xiuxiu Wu; Fengqin Yin; Fei Xu (Food Control, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

The role and regulation of SIRT1 in pulmonary fibrosis - Xinyi Ma; Mengna Jiang; Wenqian Ji; Mengjiao Yu; Can Tang; Kai Tian; Zhengnan Gao; Liling Su; Juan Tang; Xinyuan Zhao (Molecular Biology Reports, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Unveiling the dynamics of dry-and-humid, day-and-night, and compound heat waves across 209 Cities in China during 1974–2021 - Lijun Liu; Liling Chu; Youjia Liang; Jiangang Li; Miao Yu; Chao He (Urban Climate, 2024)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Optimization of Cr(VI) ion-imprinted polymer with imidazole derivatives as functional monomers and its binding mechanism - Mengyuan Huang; Yuanyuan Yang; Hui Cao; Min Yuan; Tai Ye; Liling Hao; Jinsong Yu; Fengqin Yin; Fei Xu; Xiuxiu Wu (Journal of Environmental Chemical Engineering, 2024)

Investigating the impact of watershed and local environmental variables on the spatial distribution, composition and functional diversity of benthic algal communities in the upper Red River Basin, China - Kejian He; Xuekai Feng; Changming Chen; Yu Han; Xiaoxiao Ji; Yangyidan He; Liling Yang; Yuan He; Xingcan Chen; Liqin Yan (Aquatic Sciences, 2024)

Long-term exposure to fine particulate matter constituents in relation to chronic kidney disease: evidence from a large population-based study in China - Yucen Dai; Jianzhong Yin; Sicheng Li; Jiawei Li; Xinyu Han; Quzong Deji; Ciren Pengcuo; Leilei Liu; Zhimiao Yu; Liling Chen; Linshen Xie; Bing Guo; et al. (Environmental Geochemistry and Health, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Vertical and seasonal dynamics of bacterial pathogenic communities at an aged organic contaminated site: Insights into microbial diversity, composition, interactions, and assembly processes - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Zijun Yang (Journal of Hazardous Materials, 2023)

Significant roles of core prokaryotic microbiota across soil profiles in an organic contaminated site: Insight into microbial assemblage, co-occurrence patterns, and potentially key ecological functions - Zhirui Qin; Zhenhua Zhao; Liling Xia; Guangwen Yu; Aihua Miao; Yuhong Liu (Environmental Research, 2023)

Study on Strength Characteristics of Interlayer Rocks Based on Thermal–Mechanical Coupling - Liewang Qiu; Liling Zhu; Liangfu Xie; Yongjun Qin; Jianhu Wang; Guangming Yu (Geotechnical and Geological Engineering, 2023)

NCX2 Regulates Intracellular Calcium Homeostasis and Translocation of HIF-1α into the Nucleus to Inhibit Glioma Invasion - Hongyuan Liu; Ju Yu; Liling Yang; Pengcheng He; Zongping Li (Biochemical Genetics, 2023)
Glioma is the most common tumor of the central nervous system, and its poor prognosis can be linked to hypoxia and gene inactivation. Na + /Ca 2+ exchanger 2 (NCX2) is expressed only in the normal brain and not in other tissues or glioma. We constructed a hypoxic microenvironment to more accurately understand the effect of NCX2 in glioma. Our previous experiments confirmed that NCX2 inhibited the growth of U87 cells in nude mice, indicating that NCX2 is a potential tumor suppressor gene. Malignant tumor cells are often exposed to an anoxic environment. To more accurately understand the effect of NCX2 in glioma, we constructed a hypoxic microenvironment. To detect the localization of NCX2 in transfected U87 cells, immunofluorescence was used. We tested the function of NCX2 in glioma, i.e., how it contributes to the cytosolic Ca 2+ homeostasis by X-Rhod-1. We tested the cell proliferation of NCX2 in glioma in hypoxic using Cell counting kit-8 (CCK8). Cell migration and invasion were evaluated in 24-well transwell matrigel-coated or non-matrigel-coated in hypoxia. NCX2 promoted the proliferation of U87 cells in the hypoxic microenvironment. It inhibited the invasion and migration abilities of U87 cells. We demonstrated that NCX2 was located on the cell membrane and that it reduced intracellular Ca 2+ levels and reactivated P53 and PTEN. We further demonstrated that NCX2 impaired cell invasion through the HIF-1α pathway in glioma. The results indicated that NCX2 plays a key role in glioma formation and tumor invasion functionality.

Application of the Non-dominated Sorting Genetic Algorithm II in Multi-objective Optimization of Orally Disintegrating Tablet Formulation - Jiaqi Zhang; Yu Yao; Wei Sun; Liling Tang; Xiaodong Li; Huaqing Lin (AAPS PharmSciTech, 2022)

A Systematic Approach for Liposome and Lipodisk Preclinical Formulation Development by Microfluidic Technology - Elizabeth S. Levy; Jesse Yu; Alberto Estevez; Jialin Mao; Liling Liu; Elizabeth Torres; Dennis Leung; Chun-Wan Yen (The AAPS Journal, 2021)

Aquaporin 5 is degraded by autophagy in diabetic submandibular gland - Yan Huang; Xijin Shi; Qianying Mao; Yan Zhang; Xin Cong; Xueming Zhang; Zhejing Zhang; Liling Wu; Ruolan Xiang; Guangyan Yu (Science China Life Sciences, 2018)

Epidemiological and genetic characteristics of the fifth avian influenza A(H7N9) wave in Suzhou, China, from October 2016 to April 2017 - Zefeng Dong; Yu Xia; Xuerong Ya; Liling Chen; Cheng Liu; Ruyan Wang; Qiang Shen (Virus Genes, 2018)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)